PENGARUH TRANSFORMATIONAL LEADERSHIP DAN MOTIVATION TERHADAP EMPLOYEE PERFORMANCE - Rani Merlina (PT Naureen Digital Education, 2022)
This study aims to examine the effect of transformational leadership and motivation variables on employee performance in the Lab sub-dept of PT. Pratama Abadi Industri JX both partially and simultaneously. The research method uses a survey method using a questionnaire distributed to 65 respondents. While the instrument quality testing techniques include validity and reliability tests. And data analysis techniques use descriptive analysis and correlation, while for hypothesis testing using multiple linear regression analysis. The results of this study indicate that there is no partially significant effect between transformational leadership on employee performance, but there is a partially significant effect between motivation on employee performance. While for the silmultan test there is a significant effect between transformational leadership and motivation on employee performance. Calculation of the coefficient of determination ( ) transformational leadership and motivation has an influence on employee performance of 51.2% and the remaining 48.8% is influenced by other factors. This analysis is only carried out at the Lab sub-dept and only two dimensions or variables are tested, it is expected that researchers who will conduct research in the future should expand the variables and measurement of research variables.